2016
DOI: 10.1007/s12264-016-0076-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Attenuate Acute and Chronic Itch: Peripheral and Central Mechanisms of Oxidative Stress in Pruritus

Abstract: Itch (pruritus) is one of the most disabling syndromes in patients suffering from skin, liver, or kidney diseases. Our previous study highlighted a key role of oxidative stress in acute itch. Here, we evaluated the effects of antioxidants in mouse models of acute and chronic itch and explored the potential mechanisms. The effects of systemic administration of the antioxidants N-acetyl-L-cysteine (NAC) and N-tert-butyl-α-phenylnitrone (PBN) were determined by behavioral tests in mouse models of acute itch induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 68 publications
(105 reference statements)
5
41
0
Order By: Relevance
“…Different durations of ERK activation have also been reported to induce different cell responses (Marshall, 1995). Transient ERK activation in the spinal cord has been shown to be involved in histamine-dependent itch (Zhang et al, 2014;Zhou et al, 2017). In the present study, persistent ERK activation was found in DNFB-induced chronic spontaneous itch.…”
Section: Discussionsupporting
confidence: 56%
“…Different durations of ERK activation have also been reported to induce different cell responses (Marshall, 1995). Transient ERK activation in the spinal cord has been shown to be involved in histamine-dependent itch (Zhang et al, 2014;Zhou et al, 2017). In the present study, persistent ERK activation was found in DNFB-induced chronic spontaneous itch.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies performed in human atopic asthmatic patients and in dogs with AD have suggested that vitamin E supplementation was able to decrease disease severity. Furthermore, the systemic administration of antioxidants attenuated pruritus in a mouse model . Our findings further support the idea that targeted therapies, such as antioxidant therapies, could help to reduce clinical severity in those dogs where oxidative stress could be demonstrated.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, there is evidence that increased NF‐κB activation triggers skin inflammation . Secondly, OS also has been reported to contribute to the pathogenesis of pruritus in a mouse model where it was suggested that OS is a key mechanism for pruritus via activation of transient receptor potential subtype A1 (TRPA1) channels on primary sensory neurons and neurons in dorsal root ganglia and activation of phosphorylation of extracellular signal‐regulated kinase in the spinal cord …”
Section: Discussionmentioning
confidence: 99%
“…In addition to GRP and GRPR mentioned above [27], Zhou et al reveal oxidative stress as an important mechanism of acute and chronic itch via both central and peripheral regulation. They also demonstrate that anti-oxidants are effective in treating pruritus [28]. TNF-a is one of the best-known cytokines and drives pathological pain.…”
mentioning
confidence: 94%